2008
DOI: 10.1007/s10529-008-9702-9
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of α-tocopheryl glycosides by glucosidases

Abstract: Enzymatic syntheses of water-soluble alpha-tocopheryl glycosides were carried out in di-isopropyl ether using amyloglucosidase from Rhizopus mold or beta-glucosidase isolated from sweet almond. Optimum conditions for the amyloglucosidase were: alpha-tocopherol 0.5 mmol, D-glucose 0.5 mmol, 400 activity unit (AU) amyloglucosidase, 0.2 mM pH 7 phosphate buffer and 72 h; and for the beta-glucosidase: alpha-tocopherol 0.5 mmol, D: -glucose 0.5 mmol, 110 AU beta-glucosidase, 0.1 mM pH 6 phosphate buffer and 72 h. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The 13 C-NMR spectrum of 4 exhibited the anomeric carbon signal at δ 100.7 (Table 1). This 13 C chemical shift of the anomeric carbon at δ 100.7 indicates the presence of O-glucoside in the structure of 4 [32][33][34]. From the coupling pattern of the proton signals and the chemical shifts of the carbon resonances due to the sugar moiety (Table 1), the sugar component in 4 was determined to be β-D-glucopyranose.…”
Section: Glycosylation Of Oxyresveratrol (1) and Gnetol (2) By Culturmentioning
confidence: 94%
“…The 13 C-NMR spectrum of 4 exhibited the anomeric carbon signal at δ 100.7 (Table 1). This 13 C chemical shift of the anomeric carbon at δ 100.7 indicates the presence of O-glucoside in the structure of 4 [32][33][34]. From the coupling pattern of the proton signals and the chemical shifts of the carbon resonances due to the sugar moiety (Table 1), the sugar component in 4 was determined to be β-D-glucopyranose.…”
Section: Glycosylation Of Oxyresveratrol (1) and Gnetol (2) By Culturmentioning
confidence: 94%
“…The 1 H and 13 C NMR data ( Table 3) of 8 showed great similarity to those of model compound, a-tocopherol. 28 Careful comparison of the NMR data of 8 and a-tocopherol revealed that significant differences between them resided in the nature of the substituents at C-21 on the side chain (-H in a-tocopherol; -OH in 8) and at C-4 on the benzene ring where the hydroxyl group in a-tocopherol was replaced by a 3,5-dimethylphenoxyl group in 8. The assignments of the 3,5-dimethylphenoxyl group in 8 were established by the 1 H and 13 C NMR data (Table 3), together with the HMBC correlations (Fig.…”
Section: Structure Elucidation Of New Compoundsmentioning
confidence: 99%
“…Enzymatic glycosylation can be effected by glucosidases (Sivakumar et al 2006;Vijayakumar et al 2006). Glucosidases are hydrolytic in nature, but unusual conditions involving organic solvents with little quantity of water, direct the enzymes towards glycosylation (Ponrasu et al 2008).…”
Section: Introductionmentioning
confidence: 99%